Analisis Keunggulan Bersaing Nissan di Indonesia - lim Sanny (Bina Nusantara University, 2010)
Automotive sales in Indonesia picked up sharply in 2010, and increase of prices does not lower the demand for automotive products. The large population of Indonesia and the low level of car ownership in the country suggest there is a lot of potential for expansion in the automotive industry. The aim of this research is to observe Nissan’s strategy in Indonesia to gain a spot in the top 10 of the best automotive seller in Indonesia. This research uses primary data with forecasting with monthly index to forecast the demand and to detect the selling target plans in 2010. Then, with combined porter five forces to determine the competitive strategy in the last 5 years.